Simulation of Absorption Cross Section: A Preliminary Study of Infrared Absorption Spectroscopy for Sulfur Dioxide Gas Measurement - Sharplee, Syahidah; Yaacob, Maslina (Journal of Electronic Voltage and Application, 2025)
Sulfur dioxide (SO2), an unpleasant-smelling toxic gas, is among the six common air pollutants. These gases, particularly Sulfur Dioxide, are released through the combustion of fossil fuels or other materials containing sulfur. This gas can react with other substances in the atmosphere, forming tiny particles that may enter the lungs and lead to similar adverse health effects. Previously, it has been reported that the development of sulfur dioxide gas sensor such as semiconductor, electrochemical, and others show a long response time compared to absorption spectroscopy-based sensor. Thus, the aim of this project is detection of sulfur dioxide using absorption spectroscopy technique in the infrared region. Initially, the infrared region's absorption cross-section of sulfur dioxide was simulated using the Spectralcalc.com® simulator. The validity of the simulation results was established by comparing them to previous research. The deviation of less than 1% was obtained for the value of absorption cross section. Thus, it indicates the suitability of the Spectralcalc.com® simulator for obtaining the value of absorption cross section in the infrared region. Then, simulations were conducted to analyze the effects of pressure on the absorption cross-section, ranging from 800 mbar to 1200 mbar. According to the simulation, the wavelength at 1412 cm-1 exhibited minimal pressure effect, making it conducive for accurate sulfur dioxide concentration calculation.